Penatalaksanaan Fisioterapi Pada Kasus Frozen Shoulder E.C Tendinitis Supraspinatus Sinistra Dengan Modalitas Ultrasound Dan Terapi Manipulasi Di Rs Pku Muhammadiyah Yogyakarta - Putri, Yunida Amaliya, Totok Budi Santoso, S. Fis., SPd., MPH (2015)
Background: supraspinatus tendinitis is an inflammation of the supraspinatus muscle inflammation of the supraspinatus muscle tendon. Tendinitis in the shoulder, the rotator cuff and biceps tendon inflammation can occur usually as a result of pinching of the existing structures in the vicinity. Supraspinatus tendinitis is a common cause of shoulder pain complaints. Objective: To determine the management of Ultrasound (US) to reduce pain in conditions ec Frozen Shoulder tendinitis supraspinatus and to determine the management of manipulation therapy can increase the area of motion and functional activity in conditions of Frozen Shoulder tendinitis Supsraspinatus ec. Results: After treatment for 6 times the results obtained silent pain assessment T1: 3 to T6: 1, painful motion T1: 6 be T6: 3, tenderness T1: 5 to T6: 3, increased active range of motion left S: T1 : 45-0-150, becomes S: T6: 45-0-175, F: T1: 70-0-45, becomes F: T6: 175-0-45, R (F = 90): T1: 90- 0-95, into R (F = 90): T6: 90-0-70, increase range of motion left passive S: T1: 45-0-180, becomes S: T6: 45-0-180, F: T1 : 180-0-45 be F: T6: 180-0-45, R (F = 90): T1: 90-0-55, into R (F = 90): T6: 90-0-70, increased activity functional IT: 73.7%, to T6: 40%. Methods: A case study in which patients studied and observed progress during therapy six times. Conclusion: It has been shown that administration of physiotherapy modalities on the left supraspinatus tendinitis condition with interverensi ultrasound and therapeutic manipulation can be concluded that there is a reduction in pain as measured by the VDS, and improved functional ability as measured by tubsIn.